High Performance Dye-Sensitized Solar Cells Based on Electrospun MoS2-Carbon Nanofiber Composite Counter Electrode - Sun, Hengchao; Zhou, Xianzi; Yang, Wen; Gao, Yang; Zhang, Ruopu; Liu, Jianjun; Wang, Haibao; Guo, Yan; Wang, Zheng (Frontiers in Materials, 2020)
MoS2-carbon nanofiber composites were prepared via electrospun technique with ammonium thiomolybdate(VI) and PVP. The effects of thermal pretreatment on the morphology of material were studied. The results demonstate that the composite nanofiber with pretreatment shows a uniform diameter and lots of small size MoS2 particles inside with porous structure. When the composites was used as counter electrodes in dye-sensitized solar cell, a maximum efficiency of 5.7% has been achieved due to the combination of electrical conductivity and catalysis ability from MoS2-carbon nanofiber composites.